Wireless LAN 802.11 security - Hasan-Al-Banna; Rajib, Riaz Mahmood (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2008.